Applicable Life-History and Molecular Traits for Studying the Effects of Anhydrobiosis on Aging in Tardigrades - Nagwani, Amit Kumar; Kaczmarek, Łukasz; Kmita, Hanna (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Anhydrobiosis is induced by loss of water and indicates dehydration tolerance. Survival of dehydration is possible through changes at different levels of organism organization, including a remarkable reduction in metabolic activity at the cellular level. Thus, anhydrobiosis may be regarded as an anti-aging strategy. Accordingly, two hypotheses named after popular stories, “Sleeping Beauty” and “The Picture of Dorian Gray”, were proposed to explain the effect of anhydrobiosis on aging. The two hypotheses predict the presence (The Picture of Dorian Gray) or absence (Sleeping Beauty) of observable aging symptoms for animals undergoing anhydrobiosis. Predictions of these hypotheses have rarely been tested, and the cellular level has not been addressed. Tardigrades appear to be a useful model for studying the effect of anhydrobiosis on aging, as they are able to enter and survive anhydrobiosis at any stage of life, although not with the same success for all species. In this review, we discuss anhydrobiosis and aging mechanisms as well as tardigrade diversity and indicate possible multilevel markers that can be used to study the impact of anhydrobiosis on tardigrade aging. This review provides data on tardigrade diversity that may also be useful for human aging studies.
The impact of anhydrobiosis on aging has not been widely investigated and is not completely understood. Most previous studies have explained the extraordinary capacity of anhydrobiotic animals to survive extreme conditions; however, few data are available concerning their aging patterns and underlying processes. It is also not clear whether anhydrobiosis affects aging or suppresses possible causes of death. Most invertebrate aging research has been conducted using limited animal models; there are many opportunities for tardigrades in studies of aging biology, including molecular, cellular, and life-history traits. These studies may contribute to the verification of aging theories and hypotheses such as the “Sleeping Beauty” and “The Picture of Dorian Gray”, with important applicative consequences. They may concern medicine, biotechnology, and astrobiology and result in improved anti-aging strategies and preservation of biological materials for transplantation or pharmaceutical products and dry foods.